2020
DOI: 10.1002/jmv.26674
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab in hospitalized patients with COVID‐19: Clinical outcomes, inflammatory marker kinetics, and safety

Abstract: Coronavirus disease 2019 (COVID‐19) due to infection with severe acute respiratory syndrome coronavirus 2 causes substantial morbidity. Tocilizumab, an interleukin‐6 receptor antagonist, might improve outcomes by mitigating inflammation. We conducted a retrospective study of patients admitted to the University of Washington Hospital system with COVID‐19 and requiring supplemental oxygen. Outcomes included clinical improvement, defined as a two‐point reduction in severity on a six‐point ordinal scale or dischar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 50 publications
3
34
1
2
Order By: Relevance
“…Our data contradict this assumption. Two recent analyses which included only studies with a comparator cohort support our conclusion [ 65 , 66 ]. Also, Mao and colleagues reported use of tocilizumab did not decrease risk of death possibly because of an increased risk of secondary bacterial infections [ 67 ].…”
Section: Discussionsupporting
confidence: 76%
“…Our data contradict this assumption. Two recent analyses which included only studies with a comparator cohort support our conclusion [ 65 , 66 ]. Also, Mao and colleagues reported use of tocilizumab did not decrease risk of death possibly because of an increased risk of secondary bacterial infections [ 67 ].…”
Section: Discussionsupporting
confidence: 76%
“…The relatively high occurrence of false-negative test results makes a new sampling device desirable. Other diagnostic tests include chest CT scans, on which ground-glass opacities appear as typical abnormalities for COVID-19, and analysis of for instance stools or saliva via RT-PCR for detection of current infection [ 17 , 18 ]. All these tests, however, are expensive and time consuming, require trained personnel, and, in the case of chest CT scans, expose patients to X-rays.…”
mentioning
confidence: 99%
“…Hypoalbuminemia occurs in about one-third of patients with COVID-19, particularly in those with severe disease [ 24 ]. Several studies have found a consistent association between low albumin level and an increase in both mortality and length of hospital stay [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia occurs in about one-third of patients with COVID-19, particularly in those with severe disease [ 24 ]. Several studies have found a consistent association between low albumin level and an increase in both mortality and length of hospital stay [ 24 ]. A serum albumin level < 3.5 g/dL is an independent predictor of death and increases the OR for in-hospital mortality by up to six times [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation